2009
DOI: 10.1007/s11695-009-9801-2
|View full text |Cite
|
Sign up to set email alerts
|

Results of Sleeve Gastrectomy—Data from a Nationwide Survey on Bariatric Surgery in Germany

Abstract: The complication rate during the first 2 years after SG in Germany is similar to that published in the literature. In order to improve the quality of bariatric surgery, an evaluation of data from a German multicenter trial is necessary to evaluate the position of SG in the bariatric algorithm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 36 publications
2
30
0
5
Order By: Relevance
“…[12] A prospective study by Basso et al compared results of LSG (200 patients) and BPD-DS (100 patients). [25] OSAS was present in 19% and 29% of the patients in LSG and BPD-DS groups, respectively. In this study, resolution rate of OSAS was identified in each group after one-year follow-up (56% and 50%, respectively).…”
Section: Follow-up (Mo) %Ewlmentioning
confidence: 95%
See 4 more Smart Citations
“…[12] A prospective study by Basso et al compared results of LSG (200 patients) and BPD-DS (100 patients). [25] OSAS was present in 19% and 29% of the patients in LSG and BPD-DS groups, respectively. In this study, resolution rate of OSAS was identified in each group after one-year follow-up (56% and 50%, respectively).…”
Section: Follow-up (Mo) %Ewlmentioning
confidence: 95%
“…[23,25,34] The mean %EWL ranged from 43% at 84 months after surgery in the study by Eid et al to 69% at >96 months after surgery in the study from Sarela et al, but two studies had very small number of patients. [13,38,39] Boza et al reported long-term outcomes after LSG when performed as a primary bariatric procedure.…”
Section: Follow-up (Mo) %Ewlmentioning
confidence: 96%
See 3 more Smart Citations